Pengaruh Global Brand Perception dan FOMO terhadap Impulsive Buying Konsumen Uniqlo di Indonesia - Yolanda Wulan Ivana Sitorus; Fahrisa Syahkina Lubis; Intan Lie; Erikson Saragih (Jurnal Pendidikan Ekonomi Undiksha, 2026)
The development of the global fashion industry and the increasing intensity of digital marketing have led to a higher tendency toward impulsive buying behavior among consumers. In this context, global brand perception and the psychological factor of Fear of Missing Out (FoMO) have become important determinants of purchasing behavior. This study aims to analyze the effect of global brand perception and FoMO on the impulsive buying behavior of Uniqlo consumers in Indonesia. The research employs a descriptive quantitative approach with an associative method, using accidental sampling based on the Lemeshow formula, resulting in 94 respondents as determined by the researcher. Data analysis was conducted using multiple linear regression. The results show that global brand perception and FoMO have a positive and significant effect, both partially and simultaneously, on impulsive buying behavior. These findings indicate that positive perceptions of global brands and FoMO-driven psychological impulses increase consumers’ tendency to make spontaneous purchases. This study contributes theoretically to consumer behavior research and provides practical implications for marketing strategies in the fashion retail industry.